Rapid high-throughput compatible label-free virus particle quantification method based on time-resolved luminescence - Kopra Kari; Hassan Nazia; Vuorinen Emmiliisa; Valtonen Salla; Mahran Randa; Habib Huda; Jalkanen Pinja; Susi Petri; Hytönen Vesa; Hankaniemi Minna; Ylä-Herttuala Seppo; Kakkola Laura; et al. (SPRINGER HEIDELBERG, 2022)
Viruses play a major role in modern society and create risks from global pandemics and bioterrorism to challenges in agriculture. Virus infectivity assays and genome copy number determination methods are often used to obtain information on virus preparations used in diagnostics and vaccine development. However, these methods do not provide information on virus particle count. Current methods to measure the number of viral particles are often cumbersome and require highly purified virus preparations and expensive instrumentation. To tackle these problems, we developed a simple and cost-effective time-resolved luminescence-based method for virus particle quantification. This mix-and-measure technique is based on the recognition of the virus particles by an external Eu3+-peptide probe, providing results on virus count in minutes. The method enables the detection of non-enveloped and enveloped viruses, having over tenfold higher detectability for enveloped, dynamic range from 5E6 to 3E10 vp/mL, than non-enveloped viruses. Multiple non-enveloped and enveloped viruses were used to demonstrate the functionality and robustness of the Protein-Probe method.